THE STRUGGLE OF THE OTHER: MAGGIE TULLIVER IN GEORGE ELIOT'S THE MILL ON THE FLOSS - Eta Farmacelia Nurulhady (KAJIAN SASTRA, 2010)
patriarchal sociefu belieuesinbinary oppositionof menas"subject" andu)omenes "Other" whose eistence is determined by men. Gender or the dffirentiationof roles betueen men and u)omen is a social construct that both men and u)omenmust conform to in order to be socially accepted. Maggie Tulliuer in GeorgeElliot's nouel MiIl onthe Floss isposfhone d as "the other" especially inher relationuith her brother Tom. All through her life, Maggie struggles against social rulesthat regard her as "the other" because she rs a woman and euen "doubly other"for she is dffirentlrom otherfemale characeters in general Maggie's strugglein a male dominated uorld ends uhen she fi'nally dies at Aoung age.